2022
DOI: 10.1039/d2ra01450e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liquid crystal polymer (LCP) on the structure and performance of PEEK/CF composites

Abstract: Here a liquid crystal polymer (LCP) was introduced into a PEEK/CF system as a new solution to simultaneously promote processing and mechanical performance of PEEK/CF and other polymer-based composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…These LCP resins are highly sought-after in various applications, including electronic equipment connectors, automotive components, electrical appliances, and coatings. 14 Due to their exceptional rheological and ignition resistance, LCP is frequently employed in blending with engineering plastics such as PPS, polyetherimide (PEI), and PEEK. 15 Consequently, the mechanical properties of these composites can be significantly enhanced by incorporating LCP in PPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These LCP resins are highly sought-after in various applications, including electronic equipment connectors, automotive components, electrical appliances, and coatings. 14 Due to their exceptional rheological and ignition resistance, LCP is frequently employed in blending with engineering plastics such as PPS, polyetherimide (PEI), and PEEK. 15 Consequently, the mechanical properties of these composites can be significantly enhanced by incorporating LCP in PPS.…”
Section: Introductionmentioning
confidence: 99%
“…LCP resins, recognized for their excellent fluidity and superior mechanical properties, effectively enhance the mechanical performance of polymers by increasing crystallinity. These LCP resins are highly sought‐after in various applications, including electronic equipment connectors, automotive components, electrical appliances, and coatings 14 . Due to their exceptional rheological and ignition resistance, LCP is frequently employed in blending with engineering plastics such as PPS, polyetherimide (PEI), and PEEK 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the structure-function relationships between "surface microstructure of CF-interfacial interaction between PEEK matrix and CF-molding process and macroscopic properties of final CF/PEEK composites" are discussed to realize the efficient preparation of highperformance composites. 19,20 In this paper, the factors affecting the interfacial properties of CF/PEEK composites, the surface functionalization modification methods of CF and the design & synthesis of interfacial compatibilizer are reviewed. The research progress and related academic achievements in interfacial strengthening and additive manufacturing technology of CF/PEEK composites are emphatically discussed.…”
Section: Introductionmentioning
confidence: 99%
“…There, the 3D-printed PPS/LCP samples exhibit a tensile strength of 108.5 MPa and a Young’s modulus of 25.9 GPa. A combination of a carbon fiber (CF)-reinforced PEEK with a thermotropic LCP is studied in [ 32 ]. There, it is found that strong pi–pi interactions between the aromatic rings of PEEK and LCP are beneficial since they improve the crystallization behavior of PEEK and the processability of PEEK/CF composites [ 32 ].…”
Section: Introductionmentioning
confidence: 99%